Evaluation of Paraoxonase-1 and Pentraxin-3 in the Diagnosis and Prognosis of Endometrial Cancer - Mateusz Kozłowski; Kaja Michalczyk; Grzegorz Witczak; Sebastian Kwiatkowski; Aneta Mirecka; Katarzyna Nowak; Ewa Pius-Sadowska; Bogusław Machaliński; Aneta Cymbaluk-Płoska (MDPI AG, 2022)
It is relevant to find new prognostic and diagnostic biomarkers for endometrial cancer. The study group consisted of 94 cases of endometrial cancer, the control group of 65 cases of normal endometrium. We evaluated PON1 and PTX3 serum levels. The ROC curve was plotted. The area under the curve was calculated to characterize the sensitivity and specificity of the studied parameters. Univariate and multivariate analyses were performed simultaneously using the Cox regression model. The Kaplan-Meier curve was used to assess survival. The cut-off level of PON1 was 142.6 ng/mL, with a sensitivity and specificity of 79 and 84% (p = 0.0321). The cut-off level of PTX3 was 4.2 ng/mL, with a sensitivity and specificity of 63 and 57% (p = 0.028). The favorable prognostic factor determined in serum was PON1 (for PFS: HR 0.93, 95% CI 0.86-1.03, p = 0.046; for OS: HR 0.96, 95% CI 0.89-1.08, p = 0.009). PON1 may be considered a potential biomarker in the diagnosis of endometrial cancer. Considering multivariate analysis, the PON1 serum level above the median is an independent favourable prognostic factor affecting PFS and OS. Considering Kaplan-Meier curves, longer recurrence-free survival and overall survival were found in patients with PON1 levels below the median. In view of the inconclusive results, we suggest that further studies should be conducted.